RECONSTRUCTING THE DIGITAL JOURNALISM PARADIGM ON TIKTOK: A CASE STUDY OF THE @gerakanberaninusantara ACCOUNT - Ghefira Nur Azahra; M. Yoserizal Saragih (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2026)
The diffusion of short-form video platforms has opened a new arena in which non-media actors engage in practices that resemble, and in important respects reconstitute, the norms and functions of digital journalism. This study examines how the TikTok account @gerakanberaninusantara, operated by the civic organisation Gerakan Berani Nusantara (G-BRAN), produces and distributes social and political information through platform-native communicative strategies. Employing a qualitative case study design, data were collected through systematic content observation of ten purposively sampled videos, semi-structured interviews with account administrators, and digital documentation spanning December 2025 to April 2026. Analysis followed the Miles, Huberman, and Saldaña interactive model and was theoretically grounded in Berger and Luckmann's Social Construction of Reality framework. Findings demonstrate that G-BRAN externalises organisational knowledge through visually encoded short videos; objectivates information by leveraging algorithmic distribution mechanisms including hashtags and the For You Page; and achieves audience internalisation through interactive engagement. These three social constructionist processes together constitute a discernible reconstruction of the digital journalism paradigm, in which authorial authority, presentational form, and distributional logic are all substantially transformed.